Analisis Kompetensi Profesional Guru Terhadap Prestasi Belajar Siswa Kelas VI Di SD Karuna Dipa Palu - Kadek Hariana; Rizal; Surahman; Ichsanuddin Syahputra Ilmuddin (JURNAL DIKDAS, 2025)
The purpose of this study was to describe the professional competence of teachers on the learning achievement of Grade VI students at SD Karuna Dipa Palu. This type of research is descriptive qualitative research with the research location at SD Karuna Dipa Palu with 25 grade VI students. Data collection by means of observation, interviews, questionnaires and documentation. Using data reduction analysis techniques, data display, and conclusion drawing. The results of research on teacher professional competence on the learning achievement of grade VI students at SD Karuna Dipa Palu show that class teachers already have professional competence in teaching and affect student learning achievement for the better. This can be seen from the analysis of the majority of student responses showing positive results on indicators of teacher professional competence including mastery of learning materials, understanding of students, planning and implementing learning, assessing and evaluating learning, effective communication and innovation in teaching which means teachers have good competence in teaching. In addition, the school also supports the development of teacher competence through continuous training and facilities